Phytoextraction of cadmium-contaminated soil by Celosia argentea Linn.: A long-term field study. (November 2020) - Yu, Guo; Jiang, Pingping; Fu, Xiaofeng; Liu, Jie; Sunahara, Geoffrey I.; Chen, Zhe; Xiao, He; Lin, Fanyu; Wang, Xinshuai
Abstract: Phytoextraction using Celosia argentea Linn. can potentially decontaminate Cd-contaminated soils. However, most earlier studies have been conducted at laboratory scale and for a relatively short remediation period. To evaluate the phytoextraction efficiency of C. argentea combined with different soil amendments (ammonium chloride, Bacillus megaterium, and citric acid), an 18-month field experiment was carried out in a farmland soil contaminated with 3.68 mg kg −1 Cd by mine tailings in southern China. Soil Cd concentrations were decreased by 6.34 ± 0.73% after the three harvestings (with no amendments), which was 2.27 times that of the no-planting control ( p < 0.05). Application of ammonium chloride, B. megaterium, and citric acid increased the overall Cd reduction rate in soil by 40.5%, 46.1%, and 105%, respectively. The application of citric acid decreased total Cd in soil by up to 16.9% in the rhizosphere soil and 13.0% in the bulk soil. The highest annual shoot biomass yield and Cd extraction amount reached 8.79 t ha −1 and 273 g ha −1 . Acid-soluble Cd fraction in the rhizosphere was significantly lower compared to that in the bulk soil ( p < 0.05), which indicates that mobile Cd in the rhizosphere was taken up by the roots vastly. C. argentea phytoextraction also improved soil metabolic functions by increasing the activities of soil enzymes (urease, invertase, phosphatase, and catalase). These findings demonstrate that Cd phytoextraction using C. argentea with the application of soil amendments can greatly improve the quality of Cd-contaminated soils. Graphical abstract: Image 1 Highlights: A long-term field study of Cd phytoextraction by C. argentea was performed. Cd in soils was efficiently removed by C. argentea combined with soil amendments. The Cd reduction rate in the rhizosphere was greater than that in the bulk soil. Phytoextraction increased soil enzyme activities and thus improved soil functions. Abstract : C. argentea combined with B. megaterium exhibited efficient Cd removal rates from the contaminated soil and increased soil enzyme activities in a long-term field study.